Sexual education for adolescents in freire’s perspective through culture circles - Nau, Angélica Luciana (2013)
The aim of this study is to describe and analyze educational actions and promotion of sexual health activities for adolescents in an Elementary School in Florianopolis. It is a qualitative research, combined with the methodology of Paulo Freire, consisting of the investigation about themes raised by the adolescents (adolescence, sexuality, sexually transmitted diseases and contraception) through ‘culture circles’. The survey was performed at second semester of 2011, and applied to 45 students.  As a result, the educational actions focused at the adolescent health promotion, encouraged the autonomy of the group and clarified doubts about sexuality and the construction of personality, as well as practical issues of STDs, prejudice and contraception.  The ‘culture circles’ were effective actions for sexual health education, which is consistent with the high approval rate of the activity by students.